Clinical impact of progesterone levels on HCG trigger day in a follicular long-term IVF protocol - Han, Xiao; Song, Na; Zhang, Ya; Wang, Jingjing; Zhao, Fang; Zhang, Yanping; Shi, Zhanrong; Lv, Yuzhen; Wu, Menglan; Yuan, Fang; Zhu, Guangli (Frontiers in Endocrinology, 2025)
BackgroundPrevious studies have shown that elevated progesterone (P4) levels on human chorionic gonadotropin (HCG) trigger days may affect endometrial tolerance. However, no standardized threshold has been established for the impact of late follicular phase P4 on clinical outcomes. This study aimed to assess the influence of P4 levels on the day of HCG trigger in a follicular long-term protocol on clinical outcome.MethodsThis retrospective study analyzed 889 fresh in vitro fertilization-embryo transfer cycles, each involving a single top-quality cleavage-stage embryo (CSE) or blastocyst transfer. Univariate and multivariate logistic regression analyses, threshold effect analysis, and curve fitting were carried out.ResultsA significant correlation was identified between the P4 level and both the clinical pregnancy rate ([CPR] OR: 0.54, 95% CI: 0.37 – 0.81, p = 0.003) as well as the ongoing pregnancy rate ([OPR] OR: 0.68, 95% CI: 0.46 – 0.99, p = 0.047) in blastocyst transfer. However, no significant relationship was found between P4 level and CPR or OPRs in CSE transfer. The OPR displayed a linear relationship with the P4 level in CSEs. In blastocyst transfer, the CPR followed a parabolic pattern, initially declining gradually at higher P4 levels and then dropping sharply when P4 reached ≥ 1.0 ng/mL. On the other hand, the OPR displayed a reverse U-shaped curve, increasing with P4 levels up to 1.0 ng/mL before declining at higher levels. The OPR significantly declined when the P4 level exceeded 1.0 ng/mL.ConclusionsIn blastocyst transfer cycles, the P4 level on the HCG trigger day shows a curvilinear association with the outcomes of pregnancy. The optimal threshold was found to be as 1.0 ng/mL.